Creating a public information management system to drive Riga a smart sustainable tourism destination in the post pandemic era of digital revolution - Yuanyuan Liu; Natalja Lace; Lulu Chen (Trends Economics and Management, 2022)
Purpose of the article: There are at two-folds, i.e. creating a public information management system and driving the City of Riga towards a smart sustainable tourism destination with a value-created tourism digital business model in the post pandemic era. Method: It is grounded by literature review and conceptual framework construction, and the information management system for Riga is established based on the needs of developing Riga into a smart sustainable tourism destination. Scientific aim: The aim is to identify factors of a public information management system which is storing and processing massive data with information and communication technologies (ICTs), and to illustrate factors of smart sustainable tourism destinations. Findings: These include the establishment of a framework of public information management system for Riga city, with supporting information and communication technologies (ICTs), as well as uncovering dimensions and outcomes of smart sustainable tourism destinations. The Riga public information management system will promote the city as a smart sustainable tourism destination. The dimensions of a smart tourism destination are presented, namely, smart economy, smart environment, smart governance, smart living, smart mobility, and smart people. The governance aspects include city governance, environ-urban configuration, socio-institutional structure and techno-economic, while social, environmental and economic issues are stressed. Conclusions: We present a framework of a public information management system containing functions of storing and processing massive data with six ICTs, and revealing three indicators, people, technologies, and governance, for Riga as a data-driven smart sustainable tourism destination.
Keywords: M31; Q01; R11; 650; information management system; sustainable tourism destination; smart tourism destination; smart sustainable tourism destination; post pandemic era; digital revolution